If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying x + (x + 3) = 55 Reorder the terms: x + (3 + x) = 55 Remove parenthesis around (3 + x) x + 3 + x = 55 Reorder the terms: 3 + x + x = 55 Combine like terms: x + x = 2x 3 + 2x = 55 Solving 3 + 2x = 55 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-3' to each side of the equation. 3 + -3 + 2x = 55 + -3 Combine like terms: 3 + -3 = 0 0 + 2x = 55 + -3 2x = 55 + -3 Combine like terms: 55 + -3 = 52 2x = 52 Divide each side by '2'. x = 26 Simplifying x = 26
| 6.4=1.2(4.2x) | | y/9+9=-6 | | 3k^2-192=0 | | 9-3k+2+9k=23 | | 7x=28+3x | | 19-b=7 | | 7+13z-1=5z+96-2z | | ((x^2)-10)-12=0 | | 6x+8=6x-30 | | -4x^6y^3z^2/8x^3y^-3z^2 | | A=x(12-2x) | | 35x+56=35x+56 | | x-3x-10-20=180 | | 10x-8=3x | | 2-3a+6=8+a | | (x+2)-2(2-2x)=3(x+5)-3 | | 37-3x=13-7x | | x+3x+10+20=180 | | 15y-5-6y=16 | | 35x-28/35 | | ln(2x+7)=12 | | x-3x-20=180 | | 12x^4-28x^2=0 | | 5t-12+17t= | | 4y+31=6+7y | | -6y+2=-8y-12 | | 6x-8=16x+4 | | (5x-1)+2(3x+7)=4x-1 | | x-5+2=10 | | 20+5x=15x-5-55 | | -7x+5y=-5 | | -1/3t=2 |